A Methodology Developed for Assessing the Potential Drivers of Water Losses in Natural Lakes at Country-Scale: Status of Türkiye - Firatli, Ertug; Tanik, Aysegul; Musaoglu, Nebiye; Engin, Guleda (WILEY, 2025)
This study examines key features of natural lakes within a Lake Information Database (LID) and develops a lake assessment methodology (LAM) to identify the primary drivers of temporal water surface area (WSA) changes across T & uuml;rkiye. The dominating driver for WSA changes is attributed either to natural factors or to human activities through harmonised analysis utilising LAM, which brings novelty to this study. Three lakes among the 27 with surface area over 2000 ha are displayed and discussed to show the applicability and performance of LAM that utilises remote sensing (RS) and geographical information system (GIS). The dominating factor on WSA decrease in the lakes was seen as climatic conditions in the higher altitude lakes, and human activities in the lower altitude lakes pointing out the key strength of the research. Thus, LAM offers a globally applicable and flexible methodology that produces fast results regarding the main drivers of WSA.
Keywords: climate change; geographical information system (GIS); human activities; natural lakes; remote sensing (RS); water surface area (WSA); AREA; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources